Judicial Responses to Matrimonial Incorporeal Injury under Islamic Law: Evaluating Legal Effectiveness and Remedial Challenges in Shariʿa Courts of Kano State, Nigeria, with Comparative Reflections from Malaysia - Aisha Ali Tijjani; Shuaibu Umar Gokaru (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
Matrimonial Incorporeal Injury (MII) refers to non-physical harm experienced within marriage, including verbal abuse, cruelty, neglect of maintenance, sexual deprivation, abandonment, and coercive control, all of which undermine the rights and well-being of spouses under Islamic law. Although these forms of harm are recognized within the Shariʿa legal framework, litigants often face significant evidentiary and procedural barriers in seeking legal remedies, especially in cases occurring within the private domain of marital relationships. This study evaluates judicial responses to MII in the Shariʿa courts of Kano State, Nigeria, and offers comparative reflections drawn from Malaysian practice to assess the effectiveness of the existing legal mechanisms. The study aims to evaluate the response of the Shariʿa courts in Kano State to MII cases, identify challenges in the evidentiary procedures, and compare them with the practices of Shariʿa courts in Malaysia. It also seeks to propose procedural reforms that can enhance the effectiveness of Shariʿa courts in handling MII cases. The research employs a qualitative design with a case study approach. Data is collected through the analysis of 30 cases filed in the Shariʿa Courts, Upper Shariʿa Courts, and Shariʿa Courts of Appeal in Kano from 2011 to the present. Additionally, the study compares the practices of Shariʿa courts in Kano with those in Malaysia, which are more responsive to indirect evidence such as medical and psychological reports. The findings of this study reveal that the Shariʿa courts in Kano face difficulties in handling MII cases due to burdensome evidentiary procedures and a reliance on direct evidence, which often fails to meet the needs of the victims. The comparison with Malaysian Shariʿa courts shows significant differences in responsiveness to indirect evidence, which allows victims to obtain justice more effectively. This study contributes significantly to the development of Islamic family law, particularly in the context of Shariʿa courts in Kano. By identifying the shortcomings in existing judicial procedures, the research proposes solutions to improve access to justice for MII victims, particularly women. Additionally, the comparison with Malaysia provides useful perspectives for procedural reforms that can be applied in Nigeria. These reforms are expected to improve the Shariʿa court system to offer more just and equitable protection for victims of MII.